A New Standalone Tool for DC‐Equivalent Network Generation and GIC Calculation in Power Grids With Multiple Voltage Levels - S. Marsal; J. M. Torta; V. Canillas‐Pérez; J. J. Curto (Space Weather)
Abstract Space Weather phenomena pose a major socio‐economic threat due, in part, to the vulnerability of power network transformers to geomagnetically induced currents (GIC). In 1985, Lehtinen and Pirjola (LP) provided a method to calculate GICs in a single‐voltage‐level network. The need to account for lower voltages has caused the proliferation of GIC risk assessments applied to power grids with multiple voltages. We hereby present a tool to systematically generate the direct currents (DC)‐equivalent of a multiple‐voltage‐level network. The LP and Nodal Admittance Matrix methods are the most popular schemes to compute the GIC from the resulting equivalent network by solving the circuit laws for the earthing current or the voltage at each node, respectively. A new scheme is presented here that solves the circuit laws for the current flowing between the bus nodes and the neutral point which, unlike LP, requires no (infinite‐resistance) earth connections for the buses. The number of equations/unknowns of the resulting GIC matrix equation is reduced compared to the traditional methods, thus optimizing the computational cost ‐an advantage that becomes important for large networks‐, while keeping a good condition of the design matrix associated with the inversion. Examples are shown for different test cases and a standalone computationally efficient code is provided.